Characterizing the Thermal Demands and Mobility Performance During International Wheelchair Rugby Competition - Gavel, Erica H.; Lacroix, Melissa A.; Goosey-Tolfrey, Vicky L.; Logan-Sprenger, Heather M. (Frontiers in Rehabilitation Sciences, 2022)
Objective: To determine the thermoregulatory responses and mobility performance of wheelchair rugby (WCR) players during international competition. Methods: Eleven male National Team WCR players volunteered for the study. Testing occurred during a four-game series against international competition (temp 24.7±0.7°C, relative humidity 50.1±3.6), with movement time (MT) and Tgi recorded continuously. Results: The mean maximal Tgi was 38.6±0.6°C (37.9–39.7) and did not significantly differ among Low-Class, Mid-Class, and High-Class athletes (p>0.05). Moreover, there was a strong and significant relationship between minutes played per quarter and change in Tgi (r=0.36, p=0.01). Athletes moved a total of 27:43±9:40 min:s, spent a total of 15:02±8.23 min:s in Zone 1 (53.5%), 8:19±3:20 min:s in Zone 2 (31.7%), and 5:59±1:51 min:s in Zone 3 (21.3%). There were no differences among classification in total movement time (p=0.169) or for Speed Zone 1, Zone 2, or Zone 3 (p>0.05). The relationship between peak forward speed and total movement time was strong (p=0.021, r=0.68). Conclusion: This study demonstrated that the time spent in absolute movement zones is not classification dependent, the change in core temperature is related to movement time per Q. Furthermore, peak speeds obtained on-court were linked to overall movement time which suggests athletes should warm-up before going on court.